Makoto Shinkai: cine de animación japonesa y construcción de personajes redondos - Dda. Águeda María VALVERDE-MAESTRE,Dr. José Patricio PÉREZ-RUFÍ,Dr. Francisco Javier GÓMEZ-PEREZ, (Fonseca, Journal of Communication, 2023)
This study focuses on a sample of the work of the Japanese animation director Makoto Shinkai. The first objective is the analysis of the main characters in three of his films. We apply a content analysis methodology based on the description and comparison of various dimensions of the characters from a methodological analysis proposal based on the narratological studies of cinema and literature.